Orientation Sensitive Terahertz Resonances Observed in Protein Crystals - Acbas, G.; Snell, E.; Markelz, A. G. (2012 37th International Conference on Infrared, Millimeter, and Terahertz Waves, 2012)
A method is presented for measuring anisotropic THz response for small crystals, Crystal Anisotropy Terahertz Microscopy (CATM). Sucrose CATM measurements find the expected anisotropic phonon resonances. CATM measurements of protein crystals find the expected broadband water absorption is suppressed and strong orientation and hydration dependent resonant features.
Keywords: dynamics; mode